THE COMPARATIVE LAW OF FRANCHISE AGREEMENTS IN REALIZING PROTECTION BETWEEN PARTIES - Tajuddin Noor (UNISSULA, 2023)
Franchising as a business concept regarding the granting of the use of intellectual property rights and operational activity systems by franchisors to franchisees is a legal relationship between franchisors and franchisees regulated in a franchise agreement. The purpose of this research is to analyze the Regulations regarding franchising in Indonesia and Regulations regarding franchising in other countries to compare arrangements between Indonesia and other countries. This legal research uses normative juridical research methods. The approach used is a comparative approach that involves researcher activities that begin with identifying the effect of one variable on another. franchise is a relationship based on a contract between the franchisor and the franchisee. Franchisees operate using trade names, formats, or procedures owned and controlled by the franchisor. Legal regulations in other countries often provide global trademark protection, allowing trademark owners to protect their trademarks in several countries. In Indonesian legislation, the legal protection of franchises is limited to the territory of the Republic of Indonesia.